PENGARUH PENERAPAN ISLAMIC CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK PADA ENTITAS NIRLABA YAYASAN DARUL FATAH BANGKA BELITUNG - Atika Atika (Budgeting: Jurnal Akuntansi Syariah, 2022)
Corporate governance is a basic guideline for an organization or a company in every company development. Every company must ensure that the principles of corporate governance are applied to every aspect of the business and at all levels of the company. Taxes are people's contributions to the state treasury based on the law (which can be enforced) without receiving a direct service that can be shown and which is used to pay general expenses. Taxes for companies are a burden that can reduce company profits, while for the state it is income that will be used to fund government administration. This difference in interests causes the company to manage the tax burden, both legally and illegally. A non-profit entity is an institution engaged in the social sector, of course, it must implement corporate governance according to the rules, which will affect the development of the non-profit entity itself. Entities whose funds come from donations and grants must be a concern for financial managers in terms of tax presentation and collection.